Analysis Intervention Giving Warm Compress with Boiled Ginger in the Elderly who Sufferer Osteoarthritis: Case Study - Susyanti, Susan; Windi, Windi (Nursing Case Insight Journal, 2024)
The incidence rate of osteoarthritis in Indonesia is very high that is with incidence is 5% in age not enough of 40 years, 30% occur at the age of 40-60 years, and 65% occur at the age more from 61 years. Handling non - pharmacologically can become alternative management of the elderly with Osteoarthritis, among others giving compress warm stew ginger. Case study This aim for analyze intervention care nursing with giving compress warm stew ginger for lower-level pain in the elderly Osteoarthritis sufferers. Data collection method with history taking, observation and examination physical, done analysis with compare theory with practice-based evidence (Evidence Based Practice). Participants in the study case are a elderly Osteoarthritis sufferers and instruments For measure scale painful using the Numeric Rating Scale (NRS). Intervention care nursing who has done with giving compress warm stew ginger proven can lower scale pain in someone elderly people suffering from deep osteoarthritis relative time​ fast. This is because​ ginger own Gingerol content contains cyclooxygenase that can hinder the formation of prostaglandins as pain mediators. Gingerol content and the warm feeling it creates from giving compress warm stew ginger This make vessels blood open and smooth circulation blood, so supply food and oxygen better and painful joints become reduce. Therefore​ that's a gift compress warm stew ginger can used as one of the alternative possible non - pharmacological treatment lower scale pain in osteoarthritis sufferers.